Estudo fitoquímico de Euxylophora paraensis e avaliação das substâncias isoladas frente à enzima gliceraldeído-3-fosfato desidrogenase de Trypanosoma cruzi - Isidoro, Marsele Machado (Universidade Federal de São Carlos, 2008)
This work describe the phytochemical study of bark and leaves of the specie E. paraensis (Rutaceae). This dissertation aims at contributing with the chemistry of the Rutaceae family and evaluation of the antichagasic activity of substances isolated. The phythochemical study allowed to isolate fifteen secondary metabolites belonging to different classes: two alkaloids: N-methylflindersine and skimmianine; the mixture of three steroids: β-sitosterol, stigmasterol e campestanol; the limonoid limonin; six coumarins, which are: marmesin, 8-methoximarmesin, isooxypeucedanin, prangol, isopimpinellin and xanthotoxin; and three glycosides flavonoids: quercetin-3-β-O-rhamnopyranoside, myricetin-3-β- O-rhamnopyranoside and hesperidin, while there is still no reports on the isolation of flavonoids in this specie. The isolated compounds were evaluated as the enzyme inhibitory activity in Ggapdh (glyceraldehyde-3-phosphate-dehydrogenase) of T. cruzi. However, a strategy was used for virtual screening based on physical and chemical properties of substances isolated by the computer program Volsurf 3.0. The ability of the inhibitory compounds pre-classified was tested by isothermal titration calorimetry (ITC), which has characterized the mechanism of action of active substances on the enzyme GAPDH. Through the standardized test the following compounds were tested front of GAPDH: Limonin, quercetin-3-α-O-rhamnopyranoside and prangol showed that the inhibition constant ranging between 91.8 (± 18.08) and 384.8 (145 ± , 05) μM; hesperidin and marmesin that have not submitted activity against the enzyme.
PHYTOCHEMICAL STUDY OF Euxylophora paraensis AND EVALUATION OF SUBSTANCES ISOLATED FRONT OF GLYCERALDEHYDE-3-PHOSPHATE DEHYDROGENASE OF Trypanosoma cruzi
Keywords: Euxylophora paraensis; Calorimetria; Chagas, Doença de; GAPDH; CIENCIAS EXATAS E DA TERRA::QUIMICA